The impact of virtual team characteristics on project effectiveness - Norhanim Z.,; Md. Nas’aiman M.M.Z., (Penerbit Universiti Kebangsaan Malaysia, 2019)
The effectiveness of a project team is important because it affects work quality and productivity. In these days due to increasing in globalization of organizations, most tasks and projects require contribution of an entire team. Similarly, teamwork in project virtual teams is important and personalities of the team members greatly contribute to this environment. This study was about the relationship between organizational climate, management, leadership and personality trait relationships with virtual team set the use of ICT and development of company. The study attempted to explore the type of team personality composition that mostly impacted the effectiveness of the virtual team success including the personality traits of the team members. Qualitative method of research design was employed with the findings analysed by descriptive approach. A questionnaire survey distributed to 30 respondents that were randomly selected from a renowned organization within the industry. The findings showed that the majority of the respondents agreed that the relationship between organizational climate and job satisfaction among the group members was very closely related to leadership, management and existing personality trait. In addition, the smooth use of ICT was directly specifically for virtual team itself. It could be concluded that leadership styles in organizational management based on personality selected trait.